2016
DOI: 10.1016/j.jvs.2016.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a collagen plug arterial closure device with manual compression after endovascular interventions for peripheral artery disease

Abstract: This study demonstrates that ACD use in patients with peripheral artery disease can lead to serious adverse events resulting in increased morbidity. Therefore, the potential benefits of an ACD over MC should be carefully weighed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Complication rates compared with MC as well as the safety and efficacy between devices remain comparable. [45][46][47][48][49][50][51][52] The data are variable and somewhat controversial. Whereas some studies have shown decreased complications compared with MC, 42 others have tended to show an increased risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Complication rates compared with MC as well as the safety and efficacy between devices remain comparable. [45][46][47][48][49][50][51][52] The data are variable and somewhat controversial. Whereas some studies have shown decreased complications compared with MC, 42 others have tended to show an increased risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] However, the rate of complications and patient safety is reportedly similar for VCDs compared with manual compression. [ 2 ] The various closure devices available are classified as active approximators (involve physical closure of arteriotomy site, e.g. : Starclose, Perclose Proglide), passive approximators (deploy plug/sealant/gel at arteriotomy site, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In a study comparing Angio-seal and MC applications after endovascular interventions in peripheral artery disease, Fokkema et al reported that the use of Angioseals increased the risk of developing any complications (especially hemorrhage), regardless of other parameters. The authors emphasized that the Angio-seal system should be used carefully as it can increase the complication rate [11]. Similarly, there are different studies reporting an increase in complications with VCD methods [12].…”
Section: Discussionmentioning
confidence: 99%